Eugenol Enrichment of Clove Bud Essential Oil Using Different Microwave-assisted Distillation Methods - Golmakani, Mohammad-Taghi; Zare, Mahdieh; Razzaghi, Saeedeh (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2017)
Clove bud (Syzygium aromaticum) essential oils (EOs) were extracted by hydro-distillation (HD), steam-distillation (SD), microwave-assisted hydro-distillation (MAHD), and microwave-assisted steam-distillation (MASD) methods. A comparison was made between microwave-assisted extraction and conventional extraction methods in terms of extraction kinetic, chemical composition, eugenol enrichment and antioxidant activity. Significant differences were observed between the ultimate EO yields of HD-based methods (12.98 – 13.94%) and those of SD-based methods (11.54 – 12.71%). Nonetheless, chemical compositions of the four extracted EOs were similar, but significant differences occurred among the quantity of compounds in the EOs. The ratio of eugenol per eugenyl acetate in HD-based methods (8.36 – 11.90%) was higher than those of SD-based methods (5.28 – 5.81%). These differences result from the hydrolysis of eugenyl acetate to eugenol in HD-based methods. Although, there was no significant difference between antioxidant activity of EOs extracted by microwave-assisted extraction methods and conventional-based methods but, accordingly, there were significant differences between HD-based methods and SD-based methods.